Kinematic head and trunk strategies used by hemiplegic stroke patients crossing over obstacles of different heights - Han, Jin-Tae; Lee, Jung-Hoon; Fell, Dennis W. (Journal of Physical Therapy Science, 2017)
[Purpose] The purpose of this study was to compare kinematic data regarding the head, trunk, and pelvis strategies used by individuals with hemiplegia when crossing over obstacles of different heights. [Subjects and Methods] Nine adults with hemiplegia from stroke (7 males and 2 females) participated in this study. A motion analysis system with six infrared cameras was used to measure the kinematic data of the head, trunk, and pelvis while the subjects crossed over obstacles of different heights. Repeated measures ANOVA analysis was performed to compare the resulting kinematic data. [Results] An increase in the magnitude of the kinematic data of the head, trunk, and pelvis of the hemiparetic stroke patients was observed when the height of the obstacles, which they crossed over, increased. [Conclusion] This study described the kinematic strategies, with regard to the head, trunk, and pelvis, used by hemiplegic patients crossing over obstacles of different heights. The results indicate that these kinematic strategies primarily change when the obstacle height was 20% of the height of the subjects.